Measuring the Performance of Logistics Industry in the Context of Karachi - Quais, Ifrah; Siddiqui, Danish Ahmed (Information Management and Business Review, 2017)
The Freight Forwarding and Logistics industry play a vital role in the overall economy of Pakistan. The purpose of this study is to determine the effect of the dynamic capabilities, services, capabilities, competitive advantage, and information sharing capabilities on organizational performance in the logistics industry in Karachi, Pakistan. Dynamic capabilities, services, capabilities, competitive advantage, and information sharing capabilities hypothesized as positively impacting on organizational performance. An online survey was conducted and the data were obtained from a sample size of 100 full time and part time employees from the logistics industry in Karachi. We performed multiple regression analysis to indicate all factors significant impact on organizational performance. The reliability test was also performed which showed that our study is significant. Conducting the research in a city with low literacy rate and low employee growth rate resulted in a small sample size because many people tend not to respond to online surveys.